INSILICO IDENTIFICATION OF PUTATIVE DRUG TARGETS IN MYCOPLASMA HOMINIS USING DIFFERENTIAL METABOLIC PATHWAY ANALYSIS - KANDAVELMANI ANGAMUTHU; SHANMUGHAVEL PIRAMANAYAGAM (International Journal of Pharma and Bio Sciences, 2012)
Mycoplasma hominis is a urogenital bacterium which is pathogenic for humans. Lack of cell wall and high mutation rates have made M.hominis resistant to many of the available antibiotics. Novel drug target identification is indispensable for the development of new classes of drugs to make the existing treatments more efficient and to replace drug resistance. Identification of genes that are likely to be essential for the pathogen but are non-homologous to host provides a consistent means of novel drug target identification. In the present study, differential metabolic pathway analysis approach has been applied to M.hominis to identify potential antibiotic targets. This approach identified 26 enzymes that are essential for M.hominis and non-homologous to Homo sapiens. Based on the sub cellular location and functional significance of these unique enzymes, 16 enzymes have been identified to be used as novel antibiotic targets.